Formulasi dan Evaluasi Sabun Padat Transparan dari Ekstrak Bunga Rosella (Hibiscus sabdariffa L.) - Robert Tungadi; Madania Madania; Baiq Husnul Aini (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Rosella flower is a plant with an antioxidant effect because it contains anthocyanins included in the flavonoid group. Therefore, it is essential to develop rosella flower extract in the form of soap preparations. This present work formulated and evaluated transparent solid soap preparations with 70% ethanol extract. This laboratory experimental research analyzed transparent solid soap preparations that were made of three formulas with different concentrations of active substances, namely FI (0.5%), FII (1%), FIII (2%). In addition, the evaluation of solid soap preparations involved organoleptic observations (smell, color, shape), pH test, foam height test, and irritation test on volunteers' skin. The results of quality inspection of organoleptic preparations indicated that the higher the concentration of the active substance in solid soap preparations, the less transparent the soap looks; the pH test produced 10.63-11.43; the initial foam height test resulted in 80 mm, and the final rest got 70 mm, 60 mm, and 50 mm; skin irritation tested to volunteers showed a negative reaction. The formulation in this study was formula 1, which produced the best transparent soap. It is concluded that FI, FII, and FIII soap with 70% ethanol extract of rosella flowers can be formulated as transparent solid soap.